Odpowiedź:
Metoda przeciwnych współczynników
[tex]1)\\\\\begin{cases}3x-2y=10\ \ /\cdot2\\-2x+5y=3\ \ /\cdot3\end{cases}\\\\\\+\begin{cases}6x-4y=20\\-6x+15y=9\end{cases}\\---------\\11y=29\ \ /:11\\y=\frac{29}{11}\\\\\\-2x+5\cdot\frac{29}{11}=3\\\\-2x+\frac{145}{11}=3\\\\-2x=3-\frac{145}{11} \\\\-2x=\frac{33}{11}-\frac{145}{11}\\\\-2x=-\frac{112}{11}\ \ /:(-2)\\\\x=\frac{\not112^5^6}{11}\cdot \frac{1}{\not2_{1}}\\\\x=\frac{56}{11}\\\\\begin{cases}x=\frac{56}{11} \\y=\frac{29}{11}\end{cases}[/tex]
[tex]2)\\\\\begin{cases}x+2y=8\ \ /\cdot(-3)\\3x+5y=2\end{cases}\\\\\\+\begin{cases}-3x-6y=-24\\3x+5y=2\end{cases}\\----------\\-y=-22\ \ /\cdot(-1)\\y=22\\\\\\x+2\cdot22=8\\\\x+44=8\\\\x=8-44\\\\x=-36\\\\\begin{cases}x=-36\\y=22\end{cases}[/tex]